Doktryna faszyzmu w ujęciu polskiego solidaryzmu według myśli prawnej Leopolda Caro - Fiktus, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Analyzing the works of Polish solidarists, we can fi nd many references to other — sometimes mutually exclusive — ideological currents. However, as far as the economic aspects of the solidarist doctrine are concerned, we can easily detect especially strong connections with corporatism which was also repeatedly referred to by representatives of Italian Fascism. The principal ideologue of Polish solidarism — Professor Leopold Caro — perceived corporatism as a so-called “Third Way,” constituting the ideological alternative positioned between liberalism and socialism. In all his most important works — such as Thoughts of a Japanese on Poland, Solidarism, New Ways or Towards New Poland — he repeatedly made approving references to Italian Fascism or to Benito Mussolini. His main analysis of the phenomenon of Fascism can however be found in the publication titled Social and Economic Reforms of Fascism. The most important element of the analysis of Fascism as presented by Leopold Caro was the comparison of this Italian doctrine with socialism, and particularly liberalism, regarding the issue of social and economic rights in the context of labor relations. Analyzing the social-and-economic policies undertaken by Benito Mussolini, Leopold Caro pointed out their dualist character, involving, on one hand, gaining the approval of the group of leading industrialists right after the conclusion of military hostilities when the specter of Communist revolution was seemingly looming, and, on the other, exerting a pressure on the industrialists in order to force them to recognize social rights. Another issue, which was approvingly acknowledged by the Polish solidarist, concerned the separation of economic aspects in which there existed a possibility of governmental intervention with simultaneous protection and development of private initiatives. Attempting to transplant Italian solutions onto Polish ground, Leopold Caro finally concluded that it is currently impossible to achieve due to the fact Polish society was simply not prepared for such radical changes and required substantial transformation before they could take place.
Keywords: Fascism; doctrine; Italian Fascism; legal thought; Caro, Leopold (1864-1939); solidarism